2021
DOI: 10.3390/cancers13051068
|View full text |Cite
|
Sign up to set email alerts
|

VATS Pleurectomy Decortication Is a Reasonable Alternative for Higher Risk Patients in the Management of Malignant Pleural Mesothelioma: An Analysis of Short-Term Outcomes

Abstract: Surgery is a mainstay of treatment allowing for debulking of tumor and expansion of the lung for improvement in median survival and quality of life for patients with malignant pleural mesothelioma (MPM). Although optimal surgical technique remains open for debate—extrapleural pneumonectomy (EPP) vs. pleurectomy/decortication (P/D)—minimally invasive surgery (VATS-P/D) remains underutilized in the management of MPM. We examined whether VATS-P/D is a feasible alternative to EPP and P/D. We evaluated the New York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Beside OS, therapy-associated morbidity and quality of life need to be assessed when choosing the optimal treatment modality. Several studies report a significantly reduced postoperative morbidity for patients following lung-sparing surgery compared to EPP ( 13 , 21 , 32 , 33 ). Perioperative morbidity was significantly lower in the present EPD/HITOC cohort compared to our EPP cohort and also compared to a rather high number (49%) of grade 3 or 4 adverse events reported in the SMART trial ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beside OS, therapy-associated morbidity and quality of life need to be assessed when choosing the optimal treatment modality. Several studies report a significantly reduced postoperative morbidity for patients following lung-sparing surgery compared to EPP ( 13 , 21 , 32 , 33 ). Perioperative morbidity was significantly lower in the present EPD/HITOC cohort compared to our EPP cohort and also compared to a rather high number (49%) of grade 3 or 4 adverse events reported in the SMART trial ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in the last decades, the surgical approach is mainly used as cytoreduction with improved survival, but with the necessity at least to combine with a bimodal/trimodal treatment, although the income of the novel strategies as immunotherapy, are suggesting a multimodal approach [40,62,74,75]. The debate regarding the possible surgical approach as the closest to the radicality for MPM is still opened [76,77]. In particular, the believers for EPP as the most oncologically correct approach, strongly support the theory that a near-complete surgical resection associated with chemo-or high-dose aRT may be the best treatment for earlier stages [78].…”
Section: Bimodal and Trimodal Therapy In Mpmmentioning
confidence: 99%
“…With the development of immune checkpoint therapy, Kitajima et al also demonstrated how hybrid imaging modalities could contribute to therapy response assessment and predict prognosis [ 13 ]. Among other treatment strategies, Lee et al showed how minimally invasive surgery may help manage short-term outcomes of patients with MM [ 14 ], while Di Gregorio et al revealed how metabolomic changes are associated with clinical outcomes following radical hemithoracic radiotherapy [ 15 ]. In the search for new targets, Yang et al demonstrated that the exploration of aberrant biochemical networks and potential drug vulnerabilities induced by tumor suppressor loss provide interesting prospects for the treatment of MM [ 16 ].…”
mentioning
confidence: 99%